Air velocity behavior at courtyards in the tropical climate : case studies of courtyards at IIUM Campus - Abdul Majid, Noor Hanita; Sapian, Abdul Razak; Yusof, Abdul Rahim (Universiti Teknologi MARA, 2003)
The paper presents the air velocity measurement at eight courtyards in International Islamic University Malaysia (IIUM).At IIUM, the courtyards can be categorized into two different courtyard geometry. The typologies of courtyards analyzed in this paper are the enclosed courtyard and the 'U' shape courtyard. Utilizing the data from this study, the effects of the typologies on the air velocity measurements are studied. The data collected indicated that wind flow at the courtyard could contribute in lowering the temperature and humidity, thus making the courtyard more comfortable. this factor will indirectly contribute to the saving of energy through providing comfortable naturally ventilated spaces.